Perbedaan Kadar Kuersetin pada Propolis Ekstrak Etanol dan Propolis Ekstrak Air - Nurrini Susanti Yulianti; Diding Heri Prasetyo; Sri Hartati H (Nexus Biomedika, 2012)
Background: Propolis contains flavonoids. One of them is quersetin. Solvent used is propolis extraction influence quercetin level of the extract. This research aims to determine whether there is a difference of Quercetin Level in Ethanol Extract Propolis and Water Extract Propolis. Methods: This research is an experimental research. Subject of this research is propolis from Gejen RT 3 RW 2, Kerjo, Karanganyar. The samples were carried out by purposive sampling. Concentration of quercetin is determined by using UV-Vis spectrophotometer by Prussian-blue methode. Five samples are made for each extract. The data then analized using unpaired t-test by SPSS 17 for windows. Results: Averages of quercetin level in this research are 10,04800,53798 g/mL in Ethanol extract propolis and 1,04400,06804 g/mL in Water Extract propolis with p < 0,05. Conclusions: There are differences in there is a difference of quercetin content in Ethanol Extract Propolis and Water Extract Propolis. Keywords: Propolis, Quercetin level, UV-Vis spectrophotometer, Prussian-blue